Kedudukan Hak atas Tanah Milik Yayasan yang Masih atas Nama Pendiri Yayasan: Studi terhadap Sengketa Vihara Thien En Thang - Emmy Rachmasari (International Forum of Researchers and Lecturers, 2025)
This research examines the legal vulnerability of Foundation assets whose land title certificates (SHGB) are still registered under the name of the founder or management, which can lead to disputes after the founder's death. The case of Vihara Thien En Thang reflects this issue, where conflict arose when the founder's heirs claimed the land as part of the inheritance. Through false statements, they successfully issued a Replacement HGB Certificate, while the original certificate was still held by the Foundation. The main objective of this research is to analyze the legal status of the deed of gift made by the founder to the Foundation and the legal implications of issuing the Replacement HGB Certificate based on false data. This study uses a normative legal method (juridical normative), with a statute approach and conceptual approach. Secondary data, consisting of primary, secondary, and tertiary legal sources, was collected through literature study and analyzed descriptively and qualitatively. Thus, this research aims to provide an understanding of its vulnerabilities and offer recommendations for protecting the legitimate assets of the Foundation.